Genetic variation underlying cognition and its relation with neurological outcomes and brain imaging - Knol, M; Heshmatollah, A; Cremers, L; Ikram, M; Uitterlinden, A; Van Duijn, C; Niessen, W; Vernooij, M; Ikram, M; Adams, H (Impact Journals, 2019)
Cognition in adults shows variation due to developmental and degenerative components. A recent genome-wide association study identified genetic variants for general cognitive function in 148 independent loci. Here, we aimed to elucidate possible developmental and neurodegenerative pathways underlying these genetic variants by relating them to functional, clinical and neuroimaging outcomes. This study was conducted within the population-based Rotterdam Study (N=11,496, mean age 65.3±9.9 years, 58.0% female). We used lead variants for general cognitive function to construct a polygenic score (PGS), and additionally excluded developmental variants at multiple significance thresholds. A higher PGS was related to more years of education (β=0.29, p=4.3x10-7) and a larger intracranial volume (β=0.05, p=7.5x10-4). To a smaller extent, the PGS was associated with less cognitive decline (βΔG-factor=0.03, p=1.3x10-3), which became non-significant after adjusting for education (p=1.6x10-2). No associations were found with daily functioning, dementia, parkinsonism, stroke or microstructural white matter integrity. Excluding developmental variants attenuated nearly all associations. In conclusion, this study suggests that the genetic variants identified for general cognitive function are acting mainly through the developmental pathway of cognition. Therefore, cognition, assessed cross-sectionally, seems to have limited value as a biomarker for neurodegeneration.